Konsep Peningkatan Peran Perguruan Tinggi dalam Mendukung Keberlanjutan Pengelolaan Hutan Adat di Indonesia - Suwarno, Eno; Prastyaningsih, Sri Rahayu; Hadinoto, Hadinoto; Sukma R.A, Dodi; Ikhwan, Muhammad (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2025)
Customary forests in Indonesia have very important ecological, social, and cultural values. However, their existence faces serious challenges such as tenure conflicts, ecological degradation, and policy fragmentation. This article proposes the concept of increasing the role of universities in supporting sustainable management of customary forests through the tridharma: education, research, and community service. By integrating local wisdom into the curriculum, community-based research, and transformative service, universities can strengthen the capacity of indigenous communities and fight for forest sustainability. This article also offers concrete strategies, such as the establishment of a Center for Customary Forest Studies, strengthening multi-sector collaboration networks, and educational affirmation programs for indigenous youth. With a more responsive, collaborative, and community-based approach, universities are expected to become strategic supporting institutions for equitable and sustainable customary forest conservation.